PRESTASI BELAJAR SISWA YANG DIAJARKAN OLEH GURU LULUSAN PENDIDIKAN KEGURUAN DENGAN GURU LULUSAN PENDIDIKAN NON KEGURUAN DI SMA NEGERI 5 BANDA ACEH - Farida Yahya (Program Studi Pendidikan Sejarah - Universitas Samudra, 2016)
The aims of this study are to find out the students’ ability and thedifference between students’ ability that were taught by teachers whograduated from a teachers college and the other faculty in SMA 5 BandaAceh, by giving cognitive test. To reach these points, researcher usedquantitative-comparative research. The population of this study is allstudents of SMA 5 Banda Aceh which are 257 persons. This research usedpurposive sampling with the sample is students of XI IS 1 and XI IS 3 (36persons), which consists of 17 students, taught by teachers who graduatedfrom teachers college and 19 students, taught by teachers who graduatedfrom the other faculty. This study collected the data by usingdocumentation, testing and interviewing. This study used parametricinferential statistic technique to analyze the data. And to find out thehypothesis, this study used t-test with the significant level 0.05 and dk =( The result of this research shows that t-score 3.61 >ttable 1.68, which means the ability of the students who taught by teacherswho graduated from a teachers college is better than the students whotaught by teachers who graduated from the other faculty. The averagescore of the students are 79.71 and 76.63. The different of the result iscaused of the difference education background of the teachers. Because ofthat, the competence of the teachers is different.